A Comparison of Clinical Outcomes of Endovascular Repair Versus Open Surgery for Ruptured Descending Thoracic Aorta. (April 2022) - Xie, Xinsheng; Shu, Xiaolong; Zhang, Wei; Guo, Daqiao; Zhang, Wayne W.; Wang, Lixin; Fu, Weiguo
Objective: The comparisons between thoracic endovascular aortic repair for ruptured thoracic aorta (TEVAR) and open surgery (OS) have not been well documented, although both procedures have been widely utilized. We performed a systematic review and meta-analysis to investigate the effectiveness and safety between TEVAR and OS in the repair of ruptured descending thoracic aorta. Methods: PubMed, Embase, and Cochrane Library databases were searched to find relevant studies to assess TEVAR and OS outcomes. The comparative parameters were perioperative mortality (30 day/in-hospital), 1 year mortality, paraplegia or paraparesis, renal insufficiency, stroke, pulmonary embolism, re-intervention rate, pulmonary complications, and cardiac complications. A fixed-effects model was applied to calculate the odds ratio (OR) with a 95% confidence interval (CI) on pooled outcomes from different studies. Results: Eighteen observational trials involving 2088 patients were evaluated (TEVAR=560; OS=1528). Meta-analysis showed that TEVAR in repairing the ruptured descending thoracic aorta was associated with lower perioperative mortality (OR=0.47; 95% CI: 0.34–0.66; p<0.01), 1 year mortality (OR=0.46; 95% CI: 0.29–0.75; p<0.01), renal insufficiency incidence (OR=0.56; 95% CI: 0.33–0.93; p=0.03), and pulmonary complications (OR=0.69; 95% CI: 0.52–0.92; p=0.01) when compared with OS. There was no significant difference between TEVAR and OS in terms of paraplegia, stroke, pulmonary embolism, cardiac complications, and early re-intervention rates. However, the late re-intervention rate was higher in the TEVAR group than that in the OS group. Conclusions: When repairing the ruptured descending thoracic aorta, TEVAR may be performed rapidly and safely. TEVAR is associated with lower rates of perioperative morbidity and early postoperative complications than OS.